Organizational Work Culture in Optimizing PBB-P2 Revenue: Evidence from Tanjungpinang City - Husain Al Hamid; Rumzi Samin; Edy Akhyari (Social Science Academic, 2026)
Optimizing local tax revenue has become one of the primary challenges to strengthening regional fiscal independence in Indonesia. Rural and Urban Land and Building Tax (PBB-P2) constitutes a strategic component of Local Own-Source Revenue (Pendapatan Asli Daerah/PAD), particularly following the decentralization of tax administration to local governments. Despite possessing considerable fiscal potential, the Regional Tax and Retribution Management Agency (BPPRD) of Tanjungpinang City has experienced substantial fluctuations in PBB-P2 revenue realization during the 2023–2025 period. This condition indicates that organizational factors, particularly organizational work culture, may influence the effectiveness of tax collection performance. This study aims to analyze the organizational work culture implemented by BPPRD in maximizing PBB-P2 revenue and to identify organizational efforts undertaken to improve tax collection performance. A qualitative descriptive approach is employed through in-depth interviews, observations, questionnaires, and document analysis involving structural officials, tax collection officers, and administrative staff. Data are analyzed using the interactive model consisting of data reduction, data display, and conclusion drawing. The study adopts Triguno's organizational work culture framework, emphasizing attitudes toward work, work behavior, and work discipline. The findings are expected to demonstrate that organizational work culture significantly influences employee commitment, accountability, discipline, innovation, and service quality, which ultimately determine the effectiveness of local tax collection. Furthermore, organizational transformation toward a performance-oriented work culture is anticipated to strengthen institutional capacity in achieving sustainable local revenue growth. This study contributes to the development of public administration literature by emphasizing organizational culture as a strategic determinant of local tax administration performance in decentralized government systems.